Antimicrobial Multiresistant Phenotypes of Genetically Diverse Pseudomonas Spp. Isolates Associated with Tomato Plants in Chilean Orchards - Villarreal-Diaz, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Tomatoes are susceptible to bacterial diseases, mainly related to some Pseudomonas syringae pathovars. Many Pseudomonas species are considered innocuous, but some have shown the ability to opportunistically infect tomato plants. Antimicrobial compounds have been used to control pathogenic organisms, and this can lead to environmental selection of phenotypically resistant bacteria. We assessed the diversity of Pseudomonas species associated with tomato plants from Chilean orchards and analyzed antimicrobial resistance among the isolated strains. A total of 64 Pseudomonas isolates (P. syringae, P. viridiflava, P. fluorescens, P. koreensis, P. gessardii, and P. azotoformans) were evaluated for their phenotypic resistance to seven antimicrobial compounds, including copper, streptomycin, and five other antibiotics typically not used in agriculture. The results showed that 95%, 86%, 70%, 53%, 45%, and 1.6% of the isolates were resistant to rifampin, ampicillin, copper, chloramphenicol, streptomycin, and tetracycline, respectively, with no isolates being resistant to gentamicin. A total of 96.9% of Pseudomonas isolates exhibited a multiresistant phenotype to at least two of the antimicrobials tested. The most frequent multiresistance phenotype was Cu-Str-Amp-Cm-Rif (23.4%). The presence of Pseudomonas strains tolerant to conventional bactericides, metals, and other antimicrobials makes these bacteria an emerging threat to the agriculture industry and to human health. © 2022 by the authors.